Disseminated Candida lusitaniae: Nosocomial Acquisition Secondary to an Indwelling Urinary Catheter - Ali Raja; Julia Park (Case Reports in Infectious Diseases)
Candida lusitaniae is a rare opportunistic pathogen, and its most common risk factors include immunocompromised patients often with an underlying malignancy. It commonly displays resistance to amphotericin B, and historically, echinocandins have been considered first-line treatment. We present a 77-year-old male with a history of diabetes mellitus. He was treated for cellulitis and discharged to a skilled nursing facility with an indwelling urinary catheter. Despite recommendations from the medicine team to remove the catheter, the patient refused even after discussing the risks and benefits. He returned to the hospital 3 weeks later with symptoms of dysarthria, right-sided facial droop, and right-sided weakness. Ultimately, he was determined to have fungemia and native valve endocarditis due to Candida lusitaniae stemming from his indwelling urinary catheter. He was treated with micafungin, but repeated blood cultures continued to grow C. lusitaniae, and he eventually expired following withdrawal of care. We present this case report to illustrate a rare occurence of Candida lusitaniae in a patient without typical risk factors. C. lusitaniae fungemia is an extremely uncommon disease in patients without underlying malignancy. Despite this lack of apparent, classic risk factors, our patient developed endocarditis of his native valve due to C. lusitaniae fungemia from an indwelling urinary catheter. The ability of this organism to form biofilms, and its rapid mutation rate, makes treating C. lusitaniae very difficult. The treatment of choice for C. lusitaniae endocarditis is surgical intervention due to biofilm formation on the cardiac valves. Medical treatment recommendations are currently fluconazole, which is in contrast to the historical use of echinocandins. Infection due to Candida lusitaniae, though rare, should be remembered by clinicians. This particular fungal agent is especially difficult to treat due to its multiple virulence factors. Additionally, the use of indwelling urinary catheters should only occur when proper indications are present and should be promptly discontinued when their placement is no longer necessary.